The current regulation of abortion in Spain (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The present study examines the current regulation of abortion in Spain. It pays special attention to its recent reform (2023) explaining its causes and the differences existing between the original regulation of abortion (2010) and the new one.
Keywords: Abortion; Spanish Constitution; Organic Law 2/2010 on Sexual and Reproductive Health and Abortion